Kerusakan Dan Jumlah Hemosit Udang Windu (Penaeus monodon Fab.) Yang Mengalami Zoothamniosis [The Destruction And Total Haemocyte Count Of Penaeus monodon Fab. That Infected Zoothamnium Penaei (Zoothamniosis)] - Gunanti Maharani; Sunarti Sunarti; Juni Triastuti; Tutik Juniastuti (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
Abstract Tiger shrimp (Penaeus monodon Fab.) is one of the biggest non-oil and natural gas export fisheries commodity. In the other hand, the culture of this shrimp is highly affected by infectious pathogens and disease control is ciliated protozoa, Zoothamnium penaei that play an important role as ectocommensals on the body surface of tiger shrimp and causes